A reproducible and high-throughput HPLC/MS method to separate sarcosine from α- and β-alanine and to quantify sarcosine in human serum and urine - Meyer, Tamra E; Fox, Stephen D; Issaq, Haleem J; Xu, Xia; Chu, Lisa W; Veenstra, Timothy D; Hsing, Ann W (Analytical chemistry (Washington), 2011)
While sarcosine was recently identified as a potential urine biomarker for prostate cancer, further studies have cast doubt on its utility to diagnose this condition. The inconsistent results may be due to the fact that alanine and sarcosine coelute on an HPLC reversed-phase column and the mass spectrometer cannot differentiate between the two isomers, since the same parent/product ions are generally used to measure them. In this study, we developed a high-throughput liquid chromatography-mass spectrometry (LC-MS) method that resolves sarcosine from alanine isomers, allowing its accurate quantification in human serum and urine. Assay reproducibility was determined using the coefficient of variation (CV) and intraclass correlation coefficient (ICC) in serum aliquots from 10 subjects and urine aliquots from 20 subjects across multiple analytic runs. Paired serum/urine samples from 42 subjects were used to evaluate sarcosine serum/urine correlation. Both urine and serum assays gave high sensitivity (limit of quantitation of 5 ng/mL) and reproducibility (serum assay, intra- and interassay CVs < 3% and ICCs > 99%; urine assay, intra-assay CV = 7.7% and ICC = 98.2% and interassay CV = 12.3% and ICC = 94.2%). In conclusion, this high-throughput LC-MS method is able to resolve sarcosine from α- and β-alanine and is useful for quantifying sarcosine in serum and urine samples.